Trimethyltin(IV) Bearing 3-(4-Methyl-2-oxoquinolin-1(2H)-yl)propanoate Causes Lipid Peroxidation-Mediated Autophagic Cell Death in Human Melanoma A375 Cells - Marijana P. Kasalović; Dušan Dimić; Sanja Jelača; Danijela Maksimović-Ivanić; Sanja Mijatović; Bojana B. Zmejkovski; Simon H. F. Schreiner; Tobias Rüffer; Nebojša Đ. Pantelić; Goran N. Kaluđerović (MDPI AG, 2024)
A novel trimethyltin(IV) complex (Me3SnL), derived from 3-(4-methyl-2-oxoquinolin-1(2H)-yl)propanoate ligand, has been synthesized and characterized by elemental microanalysis, UV/Vis spectrophotometry, FT-IR and multinuclear (1H, 13C and 119Sn) NMR spectroscopies. Furthermore, the structure of the ligand precursor HL was solved using SC-XRD (single-crystal X-ray diffraction). The prediction of UV/Vis and NMR spectra by quantum-chemical methods was performed and compared to experimental findings. The protein binding affinity of Me3SnL towards BSA was determined by spectrofluorometric titration and subsequent molecular docking simulations. Me3SnL has been evaluated for its in vitro anticancer activity against three human cell lines, MCF-7 (breast adenocarcinoma), A375 (melanoma) and HCT116 (colorectal carcinoma), and three mouse tumor cell lines, 4T1 (breast carcinoma), B16 (melanoma) and CT26 (colon carcinoma), using MTT and CV assays. The strong inhibition of A375 cell proliferation, ROS/RNS upregulation and robust lipid peroxidation lead to autophagic cell death upon treatment with Me3SnL.